The Effect of Visuomotor Latency on Steering Behavior in Virtual Reality - Rahimian, Pooya; Plumert, Jodie M.; Kearney, Joseph K. (Frontiers in Virtual Reality, 2021)
Visual feedback latency in virtual reality systems is inherent due to the computing time it takes to simulate the effects of user actions. Depending upon the nature of interaction and amount of latency, the impact of this latency could range from a minor degradation to a major disruption of performance. The goal of this study was to examine how visuomotor latency impacts users’ performance in a continuous steering task and how users adapt to this latency with experience. The task involved steering a bike along an illuminated path in a dark environment viewed in an HTC Vive head-mounted virtual reality display. We examined how users adapt to visuomotor latency in two different conditions: 1) when the user controlled the steering while the bike moved forward at a constant speed, and 2) when the user controlled the steering and the speed of the bike through pedaling and braking. We found that users in both conditions started with a large steering error at the beginning of exposure to visuomotor latency but then quickly adapted to the delay. We also found that when users could control their speed, they adjusted their speed based on the complexity of the path (i.e., proximity to turns) and they gradually increased their speed as they adapted to latency and gained better control over their movement. The current work supports the idea that users can adapt to visual feedback delay in virtual reality regardless of whether they control the pace of movement. The results inform the design of virtual reality simulators and teleoperation systems and give insight into perceptual-motor adaptation in the presence of latency.